Answer:
![\large\boxed{(s-2)(s+2)(s-3)=(s^2-4)(s-3)=s^3-3s^2-4s+12}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%28s-2%29%28s%2B2%29%28s-3%29%3D%28s%5E2-4%29%28s-3%29%3Ds%5E3-3s%5E2-4s%2B12%7D)
Step-by-step explanation:
![s^2-4=s^2-2^2=(s-2)(s+2)\\\\\text{used}\ a^2-b^2=(a-b)(a+b)\\\\s^2-5s+6=s^2-2s-3s+6=s(s-2)-3(s-2)=(s-2)(s-3)\\\\\text{Therefore}\ LCD(s^2-4,\ s^2-5s+6)=(s-2)(s+2)(s-3)](https://tex.z-dn.net/?f=s%5E2-4%3Ds%5E2-2%5E2%3D%28s-2%29%28s%2B2%29%5C%5C%5C%5C%5Ctext%7Bused%7D%5C%20a%5E2-b%5E2%3D%28a-b%29%28a%2Bb%29%5C%5C%5C%5Cs%5E2-5s%2B6%3Ds%5E2-2s-3s%2B6%3Ds%28s-2%29-3%28s-2%29%3D%28s-2%29%28s-3%29%5C%5C%5C%5C%5Ctext%7BTherefore%7D%5C%20LCD%28s%5E2-4%2C%5C%20s%5E2-5s%2B6%29%3D%28s-2%29%28s%2B2%29%28s-3%29)
How am I supposed to answer that if I can't get the graph to you?
Answer:
a14 = -40,960
Step-by-step explanation:
The sequence has a first term of 5 and a common ratio of -10/5 = -2, so the n-th term is given by ...
an = a1·r^(n-1)
an = 5·(-2)^(n-1)
The 14th term is then ...
a14 = 5·(-2)^(14-1) = -5·2^13 = -5·8192
a14 = -40,960
Answer:
x=2
Step-by-step explanation:
the slope is vertical meaning it is undefined.